2018
DOI: 10.7150/thno.21696
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Nanowire Platform for Highly Efficient Isolation and Direct PCR-free Colorimetric Detection of Human Papillomavirus DNA from Unprocessed Urine

Abstract: Purpose: As human papillomavirus (HPV) is primarily responsible for the development of cervical cancer, significant efforts have been devoted to develop novel strategies for detecting and identifying HPV DNA in urine. The analysis of target DNA sequences in urine offers a potential alternative to conventional methods as a non-invasive clinical screening and diagnostic assessment tool for the detection of HPV. However, the lack of efficient approaches to isolate and directly detect HPV DNA in urine has restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Taken together, these findings highlight the importance of identifying the variant to determine the best treatment strategy for ALK-positive NSCLC. [20] The NW-based cfDNA assay showed better feasibility for the detection of specific ALK fusion variants than genotyping methods used in other studies such as targeted next-generation sequencing, Sanger sequencing, and whole-exome sequencing.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Taken together, these findings highlight the importance of identifying the variant to determine the best treatment strategy for ALK-positive NSCLC. [20] The NW-based cfDNA assay showed better feasibility for the detection of specific ALK fusion variants than genotyping methods used in other studies such as targeted next-generation sequencing, Sanger sequencing, and whole-exome sequencing.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, we developed a new genotyping assay that accurately and rapidly detects small amounts of tumor-derived cell-free DNA (cfDNA) in various body fluids in patients with lung cancer or cervical cancer. [18][19][20] This assay isolates cfDNA in body fluids using nanowires (NW) and directly detects DNA variants or mutations without PCR amplification within 1 hour. Our previous studies demonstrated that this NW-based cfDNA assay can be used to detect low-abundance DNA variants in plasma cfDNA with high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two further recent studies have also been published by a research group that developed an ultrasensitive nanowire assay [ 38 , 39 ]. Both studies used polyethylenimine-conjugated nanowires (PEI-NWs) and implemented HPV DNA isolation and detection strategy in urine samples.…”
Section: Recent Developments Of Urine Hpv Testingmentioning
confidence: 99%